2004
DOI: 10.1038/sj.ijo.0802805
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in adolescents: measurements and metabolic aspects

Abstract: INTRODUCTION:Adolescence is a decisive period in human life in which important body composition changes occur. Increase of total body mass and its relative distribution are mainly related to gender and pubertal development. OBJECTIVE: This review explores the specific measurements that may be used in this age group to assess excess body fat and to define obesity and overweight. RESULTS: Identification of subjects at risk for adiposity requires simple anthropometric cutoffs for the screening of overweight and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
1
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 30 publications
2
93
1
10
Order By: Relevance
“…For this purpose and because AVENA is a large epidemiological study, we used anthropometric measurements. Data on DXA measurements were obtained in the Zaragoza's cohort (Rodríguez et al, 2004). The studied sample is representative of the real situation in Spain, with a prevalence of overweight, including obesity, of 25.69% in boys and 19.13% in girls (Moreno et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose and because AVENA is a large epidemiological study, we used anthropometric measurements. Data on DXA measurements were obtained in the Zaragoza's cohort (Rodríguez et al, 2004). The studied sample is representative of the real situation in Spain, with a prevalence of overweight, including obesity, of 25.69% in boys and 19.13% in girls (Moreno et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of body composition, it has been observed that, in each sex, annual increases in BMI were driven primarily by increases in fat free mass/ stature 2 until late adolescence, with increases in total body fat/stature 2 contributing to a larger proportion of the BMI increases in girls than in boys (Maynard et al, 2001). In a group of 280 adolescents from Zaragoza, we measured BF% by DXA (Rodríguez et al, 2004); obesity status was defined by IOTF cutoff values (Cole et al, 2000), and subjects were therefore classified into three groups: normal-weight, overweight and obese. The 85th percentile of the BF% distribution in each gender was considered as cutoff point for excess adiposity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Waist circumference seems to be the best simple anthropometric predictor for the screening of the metabolic syndrome in children and adolescents. 6,7 Recently Cole et al 8 compared the performance of different measures of body mass index (BMI) measured longitudinally in a group of kindergarten children over a 9-month period. This issue has implications for short-term studies targeting the prevention of weight gain in children at risk for obesity or the treatment of children that are already obese.…”
Section: Growthmentioning
confidence: 98%
“…BMI (weight (kg)/height (m2)) is accepted as the standard index for defining overweight and obesity due to the specificity and sensitivity it delivers [2]. It is projected that as the population becomes older, both public health and economic burdens from obesity will grow along with it [3].…”
Section: Introductionmentioning
confidence: 99%